2008
DOI: 10.1186/1477-7819-6-67
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of perineal necrotising fasciitis and associated pubic bone osteomyelitis with the vacuum assisted closure system

Abstract: Background: Acute necrotising fasciitis is a life-threatening condition, which requires urgent surgical intervention. Surgical debridement is invariably associated with large areas of tissue loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…Stage II (LRINEC scoring 6-8) may be observed for not more than 24 hours with conservative line of management and must be switched over to operative management. Stage III (LRINEC scoring ≥ 8) cases straight away need early aggressive operative line of management ranging from simple fasciotomy to aggressive repeated wound debridement, vacuum assisted closed drainage and appropriate amputations followed by delayed wound closure or reconstructive and rehabilitative procedures [36][37][38]. Results of our study as compared with those of previous similar studies are shown in TABLE 11.…”
Section: Discussionsupporting
confidence: 74%
“…Stage II (LRINEC scoring 6-8) may be observed for not more than 24 hours with conservative line of management and must be switched over to operative management. Stage III (LRINEC scoring ≥ 8) cases straight away need early aggressive operative line of management ranging from simple fasciotomy to aggressive repeated wound debridement, vacuum assisted closed drainage and appropriate amputations followed by delayed wound closure or reconstructive and rehabilitative procedures [36][37][38]. Results of our study as compared with those of previous similar studies are shown in TABLE 11.…”
Section: Discussionsupporting
confidence: 74%
“…In addition, there may be a local inflammatory response that persists beyond debridement compromising vasculature of neighbouring tissue. Use of vacuum assisted closure combined with frequent change of dressing and debridement of non-viable tissue with delayed wound closure is the mainstay of treatment for the majority of cases of necrotising fasciitis [15][16][17]. In our small series of delayed secondary reconstruction, neither patient had a wound bed that supported a graft despite repeated debridements.…”
Section: Discussionmentioning
confidence: 99%
“…The principle underlying the mechanism of VSD promoting nerve repair can be associated with the following points: (1) VSD increases blood capillary bed opening and capillaries growth [2], thus improving local oxygen supply and promotion of nerve vascularization [10]. Improved microcirculation is known to promote nerve repair [11]; (2) VSD can promote the secretion of active substance of peripheral nerve, such as substance P, VEGF, platelet-derived growth factor (PDGF), transforming growth factor (TGF-β) [3,[12][13][14].…”
Section: International Journal Of Neurosciencementioning
confidence: 99%
“…This technology is significantly different from conventional suction drainage method, such as: VSD use adjustable vacuum, the working time, and pressure can be adjusted according to actual requirements; the numerous microporous vacuseal makes the negative pressure distributed uniformly on the whole wound, therefore VSD could generate full wound drainage; the semipermeable membrane and the hydrophilic vacuseal can maintain wound moist environment and the vacuseal with 400-600 μm micropore is beneficial for tissue repair [1]. Thus, VSD could promote wound vascularization [2] and vascular endothelial growth factor (VEGF) generation [3] and relieve edema around wound significantly [4]. Since VSD may contribute to peripheral nerve regeneration, we in this study propose an experiment to investigate the impact of VSD in nerve repair.…”
Section: Introductionmentioning
confidence: 98%